Effects of Cinnamomum zeylanicum (Ceylon cinnamon) on blood glucose and lipids in a diabetic and healthy rat model - Ranasinghe, Priyanga; Perera, Sanja; Gunatilake, Mangala; Abeywardene, Eranga; Gunapala, Nuwan; Premakumara, Sirimal; Perera, Kamal; Lokuhetty, Dilani; Katulanda, P. (Pharmacognosy Research, 2012)
Objectives: To evaluate short- and long-term effects of Cinnamomum zeylanicum on food consumption, body weight, glycemic control, and lipids in healthy and diabetes-induced rats. Materials and methods: The study was conducted in two phases (Phase I and Phase II), using Sprague-Dawley rats in four groups. Phase I evaluated acute effects on fasting blood glucose (FBG) (Groups 1 and 2) and on post-oral glucose (Groups 3 and 4) blood glucose. Groups 1 and 3 received distilled-water and Groups 2 and 4 received cinnamon-extracts. Phase II evaluated effects on food consumption, body weight, blood glucose, and lipids over 1 month. Group A (n = 8, distilled-water) and Group B (n = 8, cinnamon-extracts) were healthy rats, while Group C (n = 5, distilled-water) and Group D (n = 5, cinnamon-extracts) were diabetes-induced rats. Serum lipid profile and HbA1c were measured on D-0 and D-30. FBG, 2-h post-prandial blood glucose, body weight, and food consumption were measured on every fifth day. Phase i: There was no significant difference in serial blood glucose values in cinnamon-treated group from time 0 (P > 0.05). Following oral glucose, the cinnamon group demonstrated a faster decline in blood glucose compared to controls (P < 0.05). Phase II: Between D0 and D30, the difference in food consumption was shown only in diabetes-induced rats (P < 0.001). Similarly, the significant difference following cinnamon-extracts in FBG and 2-h post-prandial blood glucose from D0 to D30 was shown only in diabetes-induced rats. In cinnamon-extracts administered groups, total and LDL cholesterol levels were lower on D30 in both healthy and diabetes-induced animals (P < 0.001). Conclusions: C. zeylanicum lowered blood glucose, reduced food intake, and improved lipid parameters in diabetes-induced rats.
Keywords: Blood glucose; Ceylon cinnamon; Cinnamomum zeylanicum; Sprague-Dawley rats; diabetes mellitus; lipids